Etching solution and method for selectively removing silicon nitride during manufacture of semiconductor device

By using an etching solution containing water, phosphoric acid solution and specific silicone compounds in the manufacturing process of 3D NAND memory equipment, the problem of insufficient etching selectivity between Si3N4 and SiO2 is solved, and high selectivity etching is achieved, reducing damage and defects of the oxide layer.

JP2025060753AInactive Publication Date: 2025-04-10VERSUM MATERIALS US LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024225001
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-11
Filing Date
2024-12-20
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the manufacturing process of 3D NAND memory equipment, it is difficult for the prior art to achieve high selective etching between Si3N4 and SiO2, resulting in increased damage and defects of the oxide layer during the etching process.

Method used

An etching solution containing water, a phosphoric acid solution and a specific silicone compound is used, which significantly improves the etching selectivity of Si3N4 to SiO2 by controlling the pH value and water solubility in the etching reaction.

Benefits of technology

High selective etching between Si3N4 and SiO2 is achieved, which significantly reduces damage and defects of the oxide layer and improves the reliability and electrical properties of the etching process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060753000001
    Figure 2025060753000001
  • Figure 2025060753000002
    Figure 2025060753000002
  • Figure 2025060753000003
    Figure 2025060753000003
Patent Text Reader

Abstract

To provide an etching solution and a method for selectively removing silicon nitride during the manufacture of a semiconductor device.SOLUTION: An etching solution and a method of using the etching solution are described herein, and the etching solution contains water, phosphoric acid solution (aqueous), organosilicon compounds described herein, and a hydroxyl group-containing water-miscible solvent. Such compositions are useful for selective removal of silicon nitride over silicon oxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This patent application is a regular patent application of U.S. Provisional Patent Application No. 62 / 816,806, filed March 11, 2019, which provisional patent application is incorporated by reference in its entirety herein. [Background technology]

[0002] Exemplary embodiments of the present invention relate to an etching composition, more specifically, a highly selective etching composition capable of selectively removing nitride films while minimizing the etch rate of oxide films, and a method for manufacturing semiconductors including an etching process using the etching composition.

[0003] Selective Si3N4 sacrificial removal is one of the critical steps for 3D NAND memory device fabrication. After the etching process, the Si3N4 is removed leaving the SiO2 core with SiO2 fins unchanged. Conventionally, Si3N4 etching can be achieved by hot phosphoric acid at 160°C, but the selectivity of Si3N4 etching to silicon or silicon oxide materials is generally low.

[0004] As semiconductor devices become more highly integrated, their reliability and electrical characteristics become more sensitive to damage or deformation of the layers that make up the semiconductor device. Thus, when an etching process is performed to selectively remove a particular material layer using an etchant, it is desirable for the etchant to have a higher etch selectivity relative to other material layers, and for the etching process to produce fewer by-products and reduce process defects. Summary of the Invention [Problem to be solved by the invention]

[0005] Thus, with such high integration, the material selectivity requirement for selective Si3N4 sacrificial removal in 3D NAND manufacturing becomes more critical in that it is desirable to leave the SiO2 layer effectively unchanged while etching the Si3N4 layer.Therefore, there is a need in the art to further reduce the SiO2 etch rate and achieve even higher Si3N4 to SiO2 selectivity. [Means for solving the problem]

[0006] In one embodiment, the present invention provides an etching solution suitable for selective removal of silicon nitride over silicon oxide from microelectronic devices, comprising water; a phosphoric acid solution (aqueous); and a compound represented by formula A: [ka] wherein R 2 and R 3 is hydrogen atom, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C5-C 12 Aryl groups, C2-C 10 Linear or branched alkenyl group, C2-C 10 R is independently selected from linear or branched alkynyl groups and functional group-containing moieties, where the functional group is at least one selected from the group consisting of vinyl, epoxy, styryl, methacyloxy, acyloxy, amino, ureido, isocyanate, isocyanurate, and mercapto; 4 But, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C3-C 10 Linear or branched alkenyl group, C3-C 10 Linear or branched alkynyl groups and C5-C 12 An etching solution is provided that includes an organosilicon compound selected from aryl groups where m=0, 1, or 2; and a hydroxyl-containing water-miscible solvent.

[0007] In another aspect, the present invention provides a method for selectively increasing the etch rate of silicon nitride relative to silicon dioxide in a composite semiconductor device (or microelectronic device) comprising silicon nitride and silicon dioxide, comprising treating the composite semiconductor device (or microelectronic device) with water; a phosphoric acid solution (aqueous); and a fluorine-containing compound of formula A: [ka] wherein R 2 and R 3 is hydrogen atom, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C5-C 12 Aryl groups, C2-C 10 Linear or branched alkenyl group, C2-C 10 R is independently selected from linear or branched alkynyl groups and functional group-containing moieties, where the functional group is at least one selected from the group consisting of vinyl, epoxy, styryl, metasiloxy, acyloxy, amino, ureido, isocyanate, isocyanurate, and mercapto; 4 But, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C3-C 10 Linear or branched alkenyl group, C3-C 10 Linear or branched alkynyl groups and C5-C 12 and an organosilicon compound selected from an aryl group, where m=0, 1, or 2; and a hydroxyl-containing water-miscible solvent; and rinsing the composite semiconductor device (or microelectronic device) after at least partial removal of the silicon nitride, wherein the etch selectivity for silicon nitride over silicon oxide is about 1000 or greater.

[0008] The embodiments of the present invention may be used alone or in combination with each other.

[0009] The present invention provides high selectivity for silicon nitride relative to silicon oxide, which is particularly important during memory device fabrication as the number of alternating layers of silicon nitride and silicon oxide in a memory device increases to greater than 30, greater than 40, greater than 48, or even more. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] All references cited in this specification, including publications, patent applications, and patents, are hereby incorporated by reference to the same extent as if each individual reference was individually and specifically indicated to be incorporated by reference and as if each was set forth in its entirety herein.

[0011] The use of the terms "a," "an," and "the," and similar referents in the context of describing the present invention (especially in the context of the claims below) are to be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The terms "comprising," "having," "including," and "containing" are to be construed as open-ended terms (i.e., meaning "including, but not limited to"), unless otherwise indicated herein. The recitation of ranges of values ​​herein is intended to serve merely as a shorthand method of referring individually to each individual value in the range, unless otherwise indicated herein, and each individual value is incorporated herein as if that value were individually recited herein. All methods described herein can be performed in any suitable order, unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "such as") provided herein is intended merely to better illustrate the invention and does not pose a limitation on the scope of the invention, unless otherwise stated. No language in the specification should be construed as indicating any undescribed element as essential to the practice of the invention.

[0012] Preferred embodiments of the invention are described herein, including the best mode known to the inventors for carrying out the invention. Variations of these preferred embodiments may become apparent to those skilled in the art upon reading the foregoing description. The inventors anticipate that those skilled in the art will employ such variations as appropriate, and the inventors intend that the invention be practiced other than as specifically described herein. Accordingly, this invention includes all modifications and equivalents of the subject matter recited in the claims appended hereto as permitted by applicable law. Moreover, any combination of the above-described elements in all possible variations thereof is encompassed by the invention unless otherwise indicated herein or otherwise clearly contradicted by context.

[0013] Generally, the present invention relates to compositions useful for selectively removing silicon nitride versus silicon oxide from microelectronic devices having such material or materials thereon during the manufacture of the microelectronic devices.

[0014] For ease of reference, "microelectronic device" corresponds to semiconductor substrates (wafers) manufactured for use in microelectronics, integrated circuit or computer chip applications, flat panel displays, phase change memory devices, solar panels, and other products including solar substrates, photovoltaic systems, and microelectromechanical systems (MEMS). Solar substrates include, but are not limited to, silicon, amorphous silicon, polycrystalline silicon, single crystal silicon, CdTe, copper indium selenide, copper indium sulfide, and gallium arsenide on gallium. Solar substrates may be doped or undoped. The term "microelectronic device" is not meant to be limiting in any manner and is understood to include any substrate that results in a microelectronic device or microelectronic assembly. The term "semiconductor device" may be used interchangeably with microelectronic device. The term "composite" can be used to describe either a semiconductor device or a microelectronic device to indicate that there is more than one type of material present in one or more layers, films, patterns, vias, etc. in or on the semiconductor device, where one layer can be a substrate, and the substrate can be a silicon wafer.

[0015] As defined herein, "low-k dielectric material" corresponds to any material used as a dielectric material in layered microelectronic devices and having a dielectric constant less than about 3.5. Preferably, the low-k dielectric material includes low polarity materials such as silicon-containing organic polymers, silicon-containing hybrid organic / inorganic materials, organosilicate glass (OSG), TEOS, fluorinated silicate glass (FSG), silicon dioxide, and carbon-doped oxide (CDO) glass. It should be understood that low-k dielectric materials can have various densities and various porosities.

[0016] As defined herein, the term "barrier material" corresponds to any material used in the art to seal metal lines, e.g., copper interconnects, to minimize diffusion of the metal, e.g., copper, into dielectric materials. Preferred barrier layer materials include tantalum, titanium, ruthenium, hafnium and other refractory metals, as well as their nitrides and silicides.

[0017] "Substantially free" is defined herein as less than 1 wt%, preferably less than 0.5 wt%, more preferably less than 0.1 wt%, more preferably less than 0.01 wt%. "Substantially free" further includes 0.000 wt%. The term "free" means 0.000 wt% or less.

[0018] As used herein, "about" is intended to correspond to ±5% of the stated value.

[0019] In all such compositions, specific components of the compositions are discussed with reference to weight percent ranges including a lower limit of zero, it is understood that such components may or may not be present in various specific embodiments of the compositions, and that in instances where such components are present, they may be present in concentrations as low as 0.001 weight percent, based on the total weight of the composition in which such component is used.

[0020] In the broad implementation of this aspect, the etching solutions of the present development comprise, consist essentially of, or consist of water, phosphoric acid, an organosilicon compound as disclosed herein, and a hydroxyl-containing water-miscible solvent.

[0021] In some embodiments, the etching solution compositions disclosed herein may be formulated to be substantially free of at least one of the following chemical compounds: hydrogen peroxide and other peroxides, ammonium ions, ammonium salts such as ammonium citrate, ammonium acetate, and ammonium sulfate, fluoride ions, hydrofluoric acid, ammonium fluoride, fluorine-containing compounds, sulfur-containing compounds, and abrasives.

[0022] In other embodiments, the etching solution compositions disclosed herein are formulated to be free of at least one of the following chemical compounds: hydrogen peroxide and other peroxides, ammonium ions, fluoride ions, and abrasives.

[0023] water The etching composition of the present development comprises water. In the present invention, water functions in various ways, for example, to dissolve one or more components of the composition, as a carrier of the components, as an aid in removing residues, as a viscosity modifier of the composition, and as a diluent.Preferably, the water used in the etching composition is deionized (DI) water.In some embodiments, as described below, water is added to the composition only by introducing other components to the composition, such as phosphoric acid, which are typically aqueous solutions or are commercially available only in aqueous solutions.

[0024] For many applications, water will comprise, for example, about 1.0 wt% to about 20 wt% of the etching composition. Other preferred embodiments of the invention can include about 5.0 wt% to about 15 wt% water. Still other preferred embodiments of the invention can include water in an amount to achieve the desired weight percentage of the other components. The amount of water in the compositions of the invention can be any amount bounded by a range having any combination of the following endpoints selected from: 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%. In alternative examples, water comprises between about 8 wt % and about 18 wt %, or between about 10 wt % and about 18 wt % of the etching composition.

[0025] phosphoric acid The etching composition of the present invention includes phosphoric acid. Phosphoric acid functions primarily to etch silicon nitride. Commercial grade phosphoric acid can be used. Typically, commercially available phosphoric acid is available as an 80% to 85% aqueous solution. In a preferred embodiment, an electronic grade phosphoric acid solution is used, and typically such electronic grade solutions have a particle count of less than 100 particles / mL, the size of the particles is 0.5 microns or less, and metal ions are present in the acid at low levels of ppm to ppb per liter. In certain embodiments, no other acids, such as hydrofluoric acid, nitric acid, or mixtures thereof, are added to the solution of the present invention.

[0026] For many applications, it is believed that the amount of phosphoric acid (aqueous solution) can comprise about 70 wt% to 99.99 wt% or about 70 wt% to about 95 wt% of the composition. The amount of phosphoric acid on a neat basis, i.e., the amount of phosphoric acid excluding water in the phosphoric acid solution added to the composition of the present invention, can be about 55 wt% to about 85 wt% or about 55 wt% to about 85 wt% of the composition. Alternatively, the amount of phosphoric acid added to the composition on a neat basis can be any amount bounded by a range having any combination of endpoints selected from the following: 55 wt%, 58 wt%, 60 wt%, 62 wt%, 65 wt%, 67 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, 74 wt%, 75 wt%, 76 wt%, 77 wt%, 78 wt%, 79 wt%, 80 wt%, 81 wt%, 82 wt%, 83 wt%, 84 wt%, and 84.96 wt%, such as from about 55 wt% to about 84.86 wt%, from about 60 wt% to about 84 wt%, from about 70 wt% to about 84 wt%, or from about 75 wt% to about 83 wt% of the composition. To be clear, when 10 grams of an 85% aqueous phosphoric acid solution is added to a composition, 8.5 grams of phosphoric acid and 1.5 grams of water are added to the composition; therefore, on an undiluted basis, 8.5 grams of phosphoric acid are added to the composition and 1.5 grams of water are added to the total amount of water in the composition.

[0027] Hydroxyl-containing water-miscible solvents The etching composition of the present invention includes a hydroxyl-containing water-miscible solvent that functions primarily to protect silicon oxide so that silicon nitride is preferentially and selectively etched, and can further improve the miscibility between phosphoric acid and any other components added to the composition.

[0028] Types of hydroxyl-containing water-miscible solvents include, but are not limited to, alkanediols and polyols (including, but not limited to, alkylene glycols), glycols, alkoxyalcohols (including, but not limited to, glycol monoethers), saturated aliphatic monohydric alcohols, unsaturated non-aromatic monohydric alcohols, and low molecular weight alcohols containing a ring structure.

[0029] Water-soluble alkanediols and polyols, such as (C2-C 20 ) alkanediols and (C3-C 20 ) Examples of alkanetriols include, but are not limited to, 2-methyl-1,3-propanediol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 2,3-butanediol, and pinacol.

[0030] Examples of water soluble alkylene glycols include, but are not limited to, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, and tetraethylene glycol.

[0031] Examples of water-soluble alkoxy alcohols include, but are not limited to, 3-methoxy-3-methyl-1-butanol, 3-methoxy-1-butanol, 1-methoxy-2-butanol, and water-soluble glycol monoethers.

[0032] Examples of water-soluble glycol monoethers include, but are not limited to, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, 1-methoxy-2-propanol, 2-methoxy-1-propanol, 1-ethoxy-2-propanol, 2-ethoxy-1-propanol, propylene glycol mono n-propyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono n-propyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monomethyl ether and ethylene glycol monobenzyl ether, diethylene glycol monobenzyl ether, and mixtures thereof.

[0033] Examples of water-soluble saturated aliphatic monohydric alcohols include, but are not limited to, methanol, ethanol, n-propyl alcohol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, 2-pentanol, tert-pentyl alcohol, 1-hexanol, and mixtures thereof.

[0034] Examples of water soluble unsaturated non-aromatic monohydric alcohols include, but are not limited to, allyl alcohol, propargyl alcohol, 2-butenyl alcohol, 3-butenyl alcohol, 4-penten-2-ol, and mixtures thereof.

[0035] Examples of water-soluble, low molecular weight alcohols containing a ring structure include, but are not limited to, alpha-terpineol, tetrahydrofurfuryl alcohol, furfuryl alcohol, 1,3-cyclopentanediol, and mixtures thereof.

[0036] For many applications, the amount of hydroxyl-containing water-miscible solvent is expected to comprise from about 1.0 wt% to about 30 wt%, or from about 3 wt% to about 25 wt% of the composition. When used, the hydroxyl-containing water-miscible solvent can comprise from about 3 wt% to about 15 wt%, or from about 5 wt% to about 15 wt% of the composition. Additionally, the amount of hydroxyl-containing water-miscible solvent in the compositions of the invention can be any amount bounded by a range having any combination of endpoints selected from the following: 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 22 wt%, 25 wt%, 27 wt%, and 30 wt%. Additional embodiments may include the hydroxyl-containing water-miscible solvent in an amount of from about 1 wt% to about 10 wt%, or from about 1 wt% to about 8 wt% of the composition.

[0037] Organosilicon Compounds The etching compositions of the present invention include an organosilicon compound that functions primarily to protect the silicon oxide so that the silicon nitride is selectively, and substantially only, etched.

[0038] In some embodiments, the organosilicon compound has Formula A: [ka] wherein R 2 and R 3 is hydrogen atom, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C5-C12 Aryl groups, C2-C 10 Linear or branched alkenyl group, C2-C 10 R is independently selected from linear or branched alkynyl groups and functional group-containing moieties, where the functional group is at least one selected from the group consisting of vinyl, epoxy, styryl, methacyloxy, acyloxy, amino, ureido, isocyanate, isocyanurate, and mercapto; 4 But, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C3-C 10 Linear or branched alkenyl group, C3-C 10 Linear or branched alkynyl groups and C5-C 12 and at least one organosilicon compound selected from aryl groups, where m=0, 1, or 2. Exemplary compounds of formula A include, but are not limited to, trimethoxymethylsilane, dimethoxydimethylsilane, triethoxymethylsilane, diethoxydimethylsilane, trimethoxysilane, dimethoxymethylsilane, di-isopropyldimethoxysilane, diethoxymethylsilane, dimethoxyvinylmethylsilane, dimethoxydivinylsilane, diethoxyvinylmethylsilane, and diethoxydivinylsilane.

[0039] For example, R 2is a functional group-containing moiety, and the functional group is at least one selected from the group consisting of vinyl, epoxy, styryl, methacyloxy, acyloxy, amino, ureido, isocyanate, isocyanurate, and mercapto. Examples of compounds of formula A containing vinyl functional groups include vinyltrimethoxysilane and vinyltriethoxysilane; examples of formula A containing epoxy functional groups include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldi ... p-styryltrimethoxysilane, which is an example of formula A containing a styryl functional group; 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane and 3-methacryloxypropyltriethoxysilane, which are examples of formula A containing a methacryloxy functional group; Examples of formula A containing amino functional groups include 3-acryloxypropyltrimethoxysilane; examples of formula A containing amino functional groups include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3 dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N-(vinylbenzyl)-2-aminopropyltriethoxysilane. aminoethyl-3-aminopropyltrimethoxysilane hydrochloride; 3-ureidopropyltrialkoxysilane, which is an example of formula A containing a ureido functional group; 3-isocyanatopropyltriethoxysilane, which is an example of formula A containing an isocyanate functional group; tris-(trimethoxysilylpropyl)isocyanurate, which is an example of formula A containing an isocyanurate functional group; and 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane, which are examples of formula A containing a mercapto functional group.

[0040] Without intending to be bound by any particular theory, it is believed that once added, the organosilicon compound reacts with water to form hydrolysis product once in the presence of water.Typically, the hydrolysis rate of etching group for silicon depends on the pH of the solution and the concentration of water.For example, the hydrolysis of trimethoxymethylsilane can proceed under both acidic and basic conditions.It is believed that the hydroxyl group in the hydrolyzed organosilicon compound either reacts with or somehow bonds with the hydroxyl group on the surface of silicon substrate to produce a protective layer, thus enabling significantly increased selectivity for silicon nitride.

[0041] For many applications, the amount of organosilicon compound is believed to comprise about 0.001 wt% to about 15 wt% of the composition. Preferably, the organosilicon compound, when used, comprises about 0.1 wt% to about 10 wt% of the composition. The amount of organosilicon compound in the composition of the present invention can be any amount bounded by a range having any combination of endpoints selected from the following: 0.001 wt%, 0.01 wt%, 0.1 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%, for example, about 0.1 wt% to about 12 wt% or about 0.1 wt% to about 8 wt% of the composition.

[0042] Silica (optional) Optionally, the etching compositions disclosed herein include silicic acid, which, when used, helps protect the silicon oxide and increases the selectivity of the silicon nitride etch.

[0043] Typically, the amount of silicic acid, when used, comprises from about 0.001 wt% to about 5.0 wt%, preferably from about 0.01 wt% to about 2.0 wt% of the composition. In other embodiments, the silicic acid, when used, comprises from about 0.02 wt% to about 0.08 wt% of the composition. The amount of silicic acid in the compositions of the invention can be any amount bounded by a range having any combination of endpoints selected from the following: 0 wt%, 0.001 wt%, 0.003 wt%, 0.004 wt%, 0.005 wt%, 0.007 wt%, 0.01 wt%, 0.03 wt%, 0.05 wt%, 0.07 wt%, 0.09 wt%, 0.1 wt%, 0.3 wt%, 0.5 wt%, 0.7 wt%, 0.9 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, and 8 wt%, such as from about 0.001 wt% to about 3 wt%, or from about 0.01 wt% to about 3 wt% of the composition.

[0044] Triethyl phosphate (optional) Optionally, the etching compositions disclosed herein include a phosphate compound, such as triethyl phosphate (TEPO) and / or trimethyl phosphate (TMPO), which, when used, functions as a supplemental solvent.

[0045] Typically, the amount of the phosphate compound, such as triethyl phosphate, when used, comprises about 0.05 wt% to about 15 wt%, preferably about 0.1 wt% to about 5 wt% of the composition. In another embodiment, triethyl phosphate, when used, comprises about 2 wt% of the composition. The amount of the phosphate compound in the composition of the present invention can be any amount bounded by a range having any combination of endpoints selected from the following: 0 wt%, 0.05 wt%, 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%, for example, about 0.5 wt% to about 8 wt% or about 1 wt% to about 6 wt% of the composition. In yet other embodiments, the composition may be substantially free or free of added phosphorus-containing components other than phosphoric acid.

[0046] Surfactant (optional) Optionally, the compositions of the present invention include at least one water-soluble non-ionic surfactant, which acts to aid in the removal of residue.

[0047] Examples of the water-soluble nonionic dispersing agent include polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene higher alcohol ethers, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene derivatives, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, polyethylene glycol monooleate, polyoxyethylene alkylamines, polyoxyethylene hydrogenated castor oil, alkyl alkanolamides, and mixtures thereof.

[0048] For most applications, the surfactant, if present, will comprise from about 0.001 wt.% to about 5 wt.% of the composition, preferably from about 0.01 wt.% to about 2.5 wt.%, and most preferably from about 0.1 wt.% to about 1.0 wt.% of the composition. The amount of surfactant in the compositions of the invention can be any value bounded by a range having any combination of endpoints selected from the following: 0 wt%, 0.001 wt%, 0.003 wt%, 0.004 wt%, 0.005 wt%, 0.007 wt%, 0.01 wt%, 0.03 wt%, 0.05 wt%, 0.07 wt%, 0.09 wt%, 0.1 wt%, 0.3 wt%, 0.5 wt%, 0.7 wt%, 0.9 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, and 5 wt%, such as from about 0.005 wt% to about 4 wt%, or from about 0.01 wt% to about 3 wt% of the composition.

[0049] In some embodiments, the compositions of the present invention are free or substantially free of any or all of the above surfactants added to the composition.

[0050] Other Optional Ingredients The etching compositions of the present invention may further comprise one or more metal chelating agents. Metal chelating agents can function to increase the capacity of the composition to retain metals in solution and facilitate dissolution of metal residues. Typical examples of chelating agents useful for this purpose include the following organic acids: ethylenediaminetetraacetic acid (EDTA), butylenediaminetetraacetic acid, (1,2-cyclohexylenediamine)tetraacetic acid (CyDTA), diethylenetriaminepentaacetic acid (DETPA), ethylenediaminetetrapropionic acid, (hydroxyethyl)ethylenediaminetriacetic acid (HEDTA), N,N,N',N'-ethylenediaminetetra(methylenephosphonic) acid (EDTMP), triethylenetetraacetic acid (TTA), and ethylenediaminetetraacetic acid (ETA). Preferred chelating agents are aminocarboxylic acids such as EDTA, CyDTA and aminophosphonic acids such as EDTMP.

[0051] For most applications, the chelating agent will be present in the composition in an amount of from about 0.1% to about 10% by weight of the composition, preferably from about 0.5% to about 5% by weight of the composition.

[0052] In some embodiments, the compositions of the present invention are free or substantially free of any or all of the above chelating agents added to the composition.

[0053] Typically, the etching solution compositions of the present invention are prepared by mixing the components together in a container at room temperature until all solids are dissolved in the water-based medium.

[0054] method In another aspect, a method for selectively enhancing the etch rate of silicon nitride relative to silicon dioxide in a composite semiconductor device (or microelectronic device) comprising silicon nitride and silicon dioxide is provided by treating a composite semiconductor device (or microelectronic device) comprising silicon nitride and silicon dioxide with water; a phosphoric acid solution (aqueous); and a fluorine-containing ... [ka] wherein R 2 and R 3 is hydrogen atom, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C5-C 12 Aryl groups, C2-C 10 Linear or branched alkenyl group, C2-C 10 R is independently selected from linear or branched alkynyl groups and functional group-containing moieties, where the functional group is at least one selected from the group consisting of vinyl, epoxy, styryl, methacyloxy, acyloxy, amino, ureido, isocyanate, isocyanurate, and mercapto; 4 But, C1~C 10 Straight chain alkyl groups, C3-C 10 Branched chain alkyl groups, C3-C 10 Cyclic alkyl groups, C3-C 10 Linear or branched alkenyl group, C3-C 10 Linear or branched alkynyl groups and C5-C 12Provided herein is a method comprising contacting a composite semiconductor device (or microelectronic device) with a composition comprising, consisting essentially of, or consisting of an organosilicon compound selected from aryl groups, where m=0, 1, or 2; and a hydroxyl-containing water-miscible solvent; and rinsing the composite semiconductor device (or microelectronic device) after at least partially removing the silicon nitride, where the etch selectivity for silicon nitride over silicon oxide is about 1000 or greater. An additional drying step may be included in the method. "At least partially removed" means at least 90% removal of material, preferably at least 95% removal. Most preferably, it means at least 99% removal using the compositions of the present development.

[0055] The contacting step can be carried out by any suitable means, such as by immersion, spraying, or by a single wafer process. The temperature of the composition during the contacting step is preferably about 100° C. to 200° C., more preferably about 140° C. to 180° C. Even more preferably, the temperature of the composition during the contacting step is about 160° C.

[0056] In preferred embodiments, the etch selectivity of silicon nitride over silicon oxide observed with the compositions of the present invention is typically about 1500 or greater, more preferably about 2000 or greater, and most preferably about 2500 or greater.

[0057] The rinsing step is carried out by rinsing the substrate with deionized water by any suitable means, such as immersion or spraying techniques. In a preferred embodiment, the rinsing step is carried out with a mixture of deionized water and a water-miscible organic solvent, such as isopropyl alcohol.

[0058] Drying may be accomplished by any suitable means, such as isopropyl alcohol (IPA) vapor drying, heat, or centripetal force.

[0059] In some embodiments, the wafer may be pretreated by contacting the wafer with diluted hydrofluoric acid (DHF) for 10 seconds to 10 minutes, where the DHF may have a composition of HO:HF=100:1. In some embodiments, the pretreatment may be performed for 3 minutes.

[0060] The features and advantages are more fully illustrated by the illustrative examples discussed below. EXAMPLES

[0061] General Procedure for Preparing the Etching Composition All compositions for the purposes of this example were prepared by mixing the components in a 250 mL beaker with a 1 inch Teflon coated stir bar. Typically, the first material added to the beaker was deionized (DI) water. Typically, phosphoric acid was added next, followed by the hydroxyl-containing water-miscible solvent, followed by the remaining components.

[0062] Substrate Composition Each 20 mm x 20 mm test coupon used in this example comprised a layer of silicon nitride, Si3N4, on a silicon substrate. A further example comprised a layer of silicon oxide, SiO2, on a silicon substrate to determine the etch rate of silicon oxide.

[0063] Processing conditions Etching tests were conducted using 100 g of the etching composition in a 250 mL beaker with a ½ inch round Teflon stir bar set at 300 rpm. The etching composition was heated to a temperature of about 160° C. on a hot plate. The test coupons were stirred for about 8 minutes (SiN x ) ~ 60 minutes (SiO x The SiN test coupons were pretreated with 1:100 DHF in a beaker at room temperature for 3 minutes, rinsed and dried, and then the test coupons were contacted with the etching composition at 160° C. for 8 minutes.

[0064] The segments were then rinsed in a DI water bath or spray for 3 min and then dried using filtered nitrogen. The etch rates of silicon nitride and silicon oxide were estimated from the change in thickness before and after etching and measured by spectroscopic ellipsometry (MG-1000, Nano-View Co., Ltd., Republic of Korea). Typical starting layer thicknesses were 4395 Å for Si3N4 and 229 Å for SiO2.

[0065] The series of tables below show the evaluation of several aspects of the compositions evaluated.

[0066] Table 1: Solvent addition [Table 1]

[0067] The process conditions for the test coupons in Table 1 were 160° C. for 20 minutes.

[0068] The results in Table 1 show that the addition of various solvents inhibited the etching of SiO2. The addition of DMSO decreased the etching rates of both Si3N4 and SiO2 without a change in selectivity. The addition of sulfolane further decreased the etching rate of SiO2 with an increase in selectivity to 54. The addition of PG and DPGME, which have -OH groups, greatly inhibited the etching rate of SiO2 with an increase in selectivity to 104 and 137, respectively. However, when PG and DPGM were added, the etchant became viscous and sticky after heating. The amount of PG and DPGME added was reduced to 10 wt% to reduce the viscosity of the etchant. The reduction in the etching rate of SiO2 was smaller with the addition of 10 wt% than with the addition of 30 wt%. The etching of Si3N4 was not significantly affected, so the etch selectivity was still higher than 85% H3PO4 alone, but was significantly lower than the 30 wt% addition of PG and DPGME. The amount of additive was reduced to 10 wt%, but the etchant solution was still viscous and sticky.

[0069] Table 2: Evaluation of hydroxyl-containing solvents [Table 2]

[0070] The process conditions for the test coupons in Table 2 were 160° C. for 20 minutes.

[0071] The etch rates of Si3N4 and SiO2 were decreased by the addition of EG and glycol. However, the inhibition of SiO2 etching was not as great as observed with PG and DPGME. The addition of α-terpineol did not significantly change the etch rates of both Si3N4 and SiO2. Finally, the increase in etch selectivity was not as great as observed with PG and DPGME. The addition of EG caused the formation of bubbles in the etchant solution. The addition of glycol made the solution viscous as the temperature was increased, but not as viscous as with PG or DPGME.

[0072] Table 3: Evaluation of organosilicon compounds [Table 3]

[0073] The process conditions for contacting each composition with the tested coupon, the results of which are listed in Table 3, were 160° C. for 20 minutes. SiN wafers were pretreated with DHF for 3 minutes, rinsed and dried.

[0074] (NH4)2SiF6 contains Si with a large amount of F, therefore the etching rate was very high. The SiO2 film was completely removed by the addition of 0.1M in 2 minutes. With the addition of silicic acid and TEOS, the etching rate of SiO2 was greatly decreased with selectivities of 268 and 312, respectively. This is due to their chemical structures similar to SiO2. Without intending to be bound by a particular theory, silicic acid and TEOS may contribute to the formation of SiO2 and reduce the etching of SiO2. Si(OH)4→SiO2+2H2O (Equilibrium in water) Si(OC2H5)4+4H2O→Si(OH)4+4C2H5OH (hydrolysis) Si(OH)4→SiO2+2H2O(condensation)

[0075] The etch rate of Si3N4 was increased by adding HF (0.03M) in the presence of silicic acid and TEOS, since high etch selectivity was obtained by the addition of silicic acid and TEOS. The addition of HF in silicic acid and TEOS increased the etch rate of SiO2 by a factor of two. However, the etch rate of Si3N4 was further increased, so the selectivity increased to 312 and 370. The addition of both HF and Si-based additives successfully increased the etch rate of Si3N4, with high etch selectivity of Si3N4 over SiO2. Thus far, the etch rate of Si3N4 of ~260 Å / min and etch selectivity of 370 are the best.

[0076] Table 4: Evaluation of silicic acid addition [Table 4]

[0077] For the results reported in Table 4, the process for treating the SiN test coupons was to pretreat with 1:100 DHF in a beaker at room temperature for 3 minutes and, after rinsing and drying, contact the test coupons with the etching solution at 160° C. for 8 minutes. x The process for treating the test coupons was to contact the test coupons with the respective etching compositions at 160° C. for 60 minutes.

[0078] With the decrease of silicic acid concentration from 0.05wt% to 0.005wt%, Si3N4 increased, but SiO2 etch rate (ER) increased more, and therefore Si3N4 / SiO2 selectivity decreased. H3PO4+0.005wt% silicic acid increased SiO2 etch rate by 20 times and Si3N4 etch rate by ~9% compared to H3PO4+0.05wt% silicic acid. It is inferred that the concentration of silicic acid should be near 0.05wt% to have an etch selectivity of 2000:1. However, the silicic acid containing chemistry showed oxide regrowth (on silicon oxide), which caused clogging problems (meaning that the silicon nitride layer was blocked by the regrowth, preventing the etching composition from reaching the silicon nitride layer in the patterned structure).

[0079] Table 5: Trimethoxymethylsilane (TMMS) addition [Table 5]

[0080] For the results reported in Table 5, the process for treating the SiN test coupons was to pretreat with 1:100 DHF in a beaker at room temperature for 3 minutes, and then contact the test coupons with the respective etching compositions at 160° C. for 8 minutes after rinsing and drying. x The process for treating the test coupons was to contact the test coupons with the respective etching compositions at 160° C. for 60 minutes.

[0081] In the case of 2 wt% TMMS, the etch selectivity was higher than the target selectivity of 2000:1. H3PO4 + 1.59 wt% TMMS did not meet the 2000:1 selectivity because the etch rate of SiO2 was more increased. No oxide regrowth and clogging issues were observed on the patterned features by treatment with TMMS-containing chemistries.

[0082] Table 6 [Table 6]

[0083] For the results reported in Table 6, the process for treating the SiN test coupons was to pretreat with 1:100 DHF in a beaker at room temperature for 3 minutes, rinse and dry the test coupons, and then contact the test coupons with the respective etching compositions at 160° C. for 8 minutes. x The process for treating the test coupons was to contact the test coupons with each etching composition at 160° C. for 60 minutes without any pretreatment step.

[0084] As-prepared examples YL-001 and YL-002, except for A1, were transparent but became slightly opaque after 24 h of stirring. Both became transparent after boiling at 160° C. YL-002 showed a selectivity of 2760, which was higher than the target selectivity of 2000:1. YL-001 showed a lower selectivity of 782, because the SiO2 etch rate was three times higher than YL-002. As-prepared example 119A was transparent but became slightly opaque after 24 h of stirring. It became transparent after boiling at 160° C. and was still transparent after cooling to room temperature. Example 119B contained 1.2 wt % TMMS and was transparent at all four time points. Examples 119A and 119B showed selectivities of 1430 and 919, respectively, which were lower than the target selectivity of 2000:1. As the concentration of TMMS added to H3PO4 + 3wt%TEPO decreased, both the etch rates of Si3N4 and SiO2 increased. Because the increase in the etch rate of SiO2 was greater than that of Si3N4, the etch selectivity decreased with decreasing TMMS concentration.

[0085] Table 7 [Table 7]

[0086] For the results reported in Table 7, the process for treating the SiN test coupons was to pretreat with 1:100 DHF in a beaker at room temperature for 3 minutes, and then contact the test coupons with the respective etching compositions at 160° C. for 8 minutes after rinsing and drying the test coupons. x The process for treating the test coupons was to contact the test coupons with each etching composition at 160° C. for 60 minutes without any pretreatment step.

[0087] Example 119G was opaque and became cloudy after 24 h of stirring. It became clear after boiling at 160° C. and was still clear after cooling to room temperature. Example 119E was clear but became cloudy after 24 h of stirring. It became clear after boiling at 160° C. and was still clear after cooling to room temperature. Example 119N was clear but became opaque after 24 h of stirring. It became clear after boiling at 160° C. and was still clear after cooling to room temperature. Example 119G showed a selectivity of 1480, which was lower than the target selectivity. Example 119E showed a selectivity of 2920, which was higher than the target selectivity of 2000:1. Example 119N showed a selectivity of 2071, which was higher than the target selectivity of 2000:1. Although the added solvent with lower polarity showed better miscibility (ethyl acetate>ethanol>acetic acid), Example 119E showed better selectivity, so the following test focused on investigating the effect from alcohol. In some embodiments, solvents with polarity less than 0.8, less than 0.7, less than 0.6, less than 0.5, less than 0.4, or less than 0.3 are preferred, with water having a polarity of 1. Additionally or alternatively, in some embodiments, solvents with less than 10 carbons, less than 8 carbons, or less than 7 carbons may be preferred.

[0088] Table 8 [Table 8]

[0089] For the results reported in Table 8, the process for treating the SiN test coupons was to pretreat with 1:100 DHF in a beaker at room temperature for 3 minutes, and then contact the test coupons with the respective etching compositions at 160° C. for 8 minutes after rinsing and drying the test coupons. x The process for treating the test coupons was to contact the test coupons with each etching composition at 160° C. for 60 minutes without any pretreatment step.

[0090] Example 119M was slightly opaque and became more opaque after 24 h of stirring. It was still opaque and yellowish even after boiling at 160° C. and cooling to room temperature. Example 119P was clear but became opaque after 24 h of stirring. It was clear after boiling at 160° C. and still transparent after cooling to room temperature (RT). Example 119Q was clear and still transparent after 24 h of stirring. In addition, it was slightly yellowish after boiling at 160° C. and cooling to room temperature. Example 119M showed a selectivity of 2114, which is higher than the target selectivity of 2000:1. Example 119P showed a selectivity of 1129 Å / min, which is lower than the target selectivity. Example 119Q showed a selectivity of 2550 Å / min, which is higher than the target selectivity of 2000:1. Example 119Q met the target selectivity and showed good miscibility. In addition, application of Example 119Q to the patterned structure completely removes the SiN layer while removing the SiO x There was no evidence of layer thinning or oxide regrowth.

[0091] Table 9: Application of selected formulations Table 9A: Patterned wafers [Table 9A] Table 9B: Blanket wafer (Si3N 48 min, SiO2 1 hr) [Table 9B]

[0092] The foregoing description is primarily for purposes of illustration, and while the present invention has been shown and described with reference to exemplary embodiments thereof, it should be understood by those skilled in the art that the foregoing and various other changes, omissions and additions in form and detail thereof may be made therein without departing from the spirit and scope of the present invention.

Claims

1. 1. An etching solution suitable for selective removal of silicon nitride relative to silicon oxide from a microelectronic device, comprising: Water; Phosphoric acid solution (aqueous); Formula A: 【Chemistry 1】 wherein R 2 and R 3 is a hydrogen atom, C 1 ~C 10 Straight chain alkyl group, C 3 ~C 10 Branched chain alkyl group, C 3 ~C 10 Cyclic alkyl group, C 5 ~C 12 Aryl group, C 2 ~C 10 A linear or branched alkenyl group, C 2 ~C 10 are each independently selected from linear or branched alkynyl groups and functional group-containing moieties, where the functional group is at least one selected from the group consisting of vinyl, epoxy, styryl, methacyloxy, acyloxy, amino, ureido, isocyanate, isocyanurate, and mercapto; R 4 But, C 1 ~C 10 Straight chain alkyl group, C 3 ~C 10 Branched chain alkyl group, C 3 ~C 10 Cyclic alkyl group, C 3 ~C 10 A linear or branched alkenyl group, C 3 ~C 10 Linear or branched alkynyl groups and C 5 ~C 12 an organosilicon compound selected from aryl groups, where m=0, 1 or 2; Hydroxyl-containing water-miscible solvent 1. An etching solution comprising:

2. 2. The etching solution of claim 1, wherein the hydroxyl-containing water-miscible solvent is selected from the group consisting of alkanediols or polyols, glycols, alkoxyalcohols, saturated aliphatic monohydric alcohols, unsaturated non-aromatic monohydric alcohols, and alcohols containing a ring structure.

3. 3. The etching solution of claim 2, wherein the hydroxyl group-containing water-miscible solvent is an alkanediol or polyol and is selected from the group consisting of 2-methyl-1,3-propanediol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 2,3-butanediol and pinacol.

4. 3. The etching solution of claim 2, wherein the hydroxyl-containing water-miscible solvent is a glycol and is selected from the group consisting of ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, and tetraethylene glycol.

5. 3. The etching solution of claim 2, wherein the hydroxyl-containing water-miscible solvent is an alkoxy alcohol and is selected from the group consisting of 3-methoxy-3-methyl-1-butanol, 3-methoxy-1-butanol, 1-methoxy-2-butanol, and glycol monoethers.

6. 3. The etching solution of claim 2, wherein the hydroxyl group-containing water-miscible solvent is a saturated aliphatic monohydric alcohol selected from the group consisting of methanol, ethanol, n-propyl alcohol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, 2-pentanol, tert-pentyl alcohol, and 1-hexanol.

7. 3. The etching solution of claim 2, wherein the hydroxyl-containing water-miscible solvent is an unsaturated non-aromatic monohydric alcohol selected from the group consisting of allyl alcohol, propargyl alcohol, 2-butenyl alcohol, 3-butenyl alcohol, and 4-penten-2-ol.

8. 6. The etching solution according to claim 5, wherein the hydroxyl group-containing water-miscible solvent is a glycol monoether and is selected from the group consisting of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, 1-methoxy-2-propanol, 2-methoxy-1-propanol, 1-ethoxy-2-propanol, 2-ethoxy-1-propanol, propylene glycol mono n-propyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono n-propyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monobenzyl ether and diethylene glycol monobenzyl ether.

9. 3. The etching solution according to claim 2, wherein the hydroxyl group-containing water-miscible solvent is an alcohol containing a ring structure and is selected from the group consisting of α-terpineol, tetrahydrofurfuryl alcohol, furfuryl alcohol and 1,3-cyclopentanediol.

10. 2. The etching solution of claim 1, wherein the hydroxyl-containing water-miscible solvent is dipropylene glycol monoethyl ether (DPGME).

11. 11. The etching solution of claim 10, wherein dipropylene glycol monoethyl ether (DPGME) is present in an amount of about 5 wt% to about 15 wt%.

12. The etching solution according to any one of claims 1 to 11, wherein the organosilicon compound is at least one selected from the group consisting of trimethoxymethylsilane, dimethoxydimethylsilane, triethoxymethylsilane, diethoxydimethylsilane, trimethoxysilane, dimethoxymethylsilane, diisopropyldimethoxysilane, diethoxymethylsilane, dimethoxyvinylmethylsilane, dimethoxydivinylsilane, diethoxyvinylmethylsilane, and diethoxydivinylsilane.

13. 13. The etching solution of claim 12, wherein the organosilicon compound is trimethoxymethylsilane.

14. The etching solution according to any one of claims 1 to 13, further comprising silicic acid.

15. 1. A method for selectively enhancing the etch rate of silicon nitride relative to silicon dioxide in a microelectronic device comprising silicon nitride and silicon dioxide, comprising: contacting a microelectronic device comprising silicon nitride and silicon dioxide with an etching solution according to any one of claims 1 to 14; rinsing the microelectronic device after at least partially removing the silicon nitride; wherein the etch selectivity for silicon nitride over silicon oxide is about 100 or greater.

16. The method of claim 15 further comprising the step of drying the microelectronic device.

17. The method of claim 15, wherein the etch selectivity for silicon nitride over silicon oxide is from about 100 to about 5000.

18. The method of claim 15, wherein the etch selectivity for silicon nitride over silicon oxide is from about 125 to about 5000.

19. 16. The method of claim 15, wherein the contacting step is carried out at a temperature of about 160°C.